Proportion of land transfer proceeds for rural development, the rural household income, and the debt risk of the rural households in China - Zhu, Liya; Ma, Zhida; Liu, Jianxu; Gao, Lemin (Frontiers in Sustainable Food Systems, 2024)
From the perspective of rural household income, this paper discusses the relationship between the proportion of land transfer proceeds for rural development and the debt risk of rural households and carries out the empirical testing by using a two-way fixed-effects model based on the data from the Chinese Household Finance Survey (CHFS) and the data matching the prefecture-level city data. The study suggests that the debt risk of rural households can be inhibited significantly in case of an increase in the proportion of proceeds from land transfer supporting rural development, and there is a “U”-shaped relationship between the proportion and the risk, which indicates that the proportion should be controlled reasonably to maximum the use efficiency of land transfer fund, and according to the system analysis, the increase in the proportion can enhance the debt-repayment ability of the rural households and reduce their debt risk by increasing their transfer income and agriculture income. Moreover, thus, this paper is of great importance for resolving the debt risk of rural households, consolidating the achievements of poverty alleviation, preventing large-scale relapse into poverty, and promoting rural revitalization.